2007
DOI: 10.1087/095315107779490661
|View full text |Cite
|
Sign up to set email alerts
|

E‐prints and journal articles in astronomy: a productive co‐existence

Abstract: Are the e‐prints (electronic preprints) from the arXiv repository being used instead of journal articles? We show that the e‐prints have not undermined the usage of journal papers from the four core journals in astrophysics. As soon as the journal article is published, the astronomical community prefers to read it and the use of e‐prints through the NASA Astrophysics Data System drops to zero. This suggests that most astronomers have access to institutional subscriptions and that they choose to read the journa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 6 publications
4
22
0
1
Order By: Relevance
“…These embargoes are applied in order to avoid putative reductions in subscription income due to such self-archiving." However, empirical evidence fails to support this 'obvious' claim, and we refer you to Berners-Lee et al, 2005;Swan, 2005;Henneken et al, 2007, Houghton et al, 2010, Bernius et al, 2013, and the Committee ), which all indicate that not only is there no loss of subscription for Economic Development, 2012 income from green open access, but that both can indeed coexist as a sustainable business model for publishers. Furthermore, there is little evidence to support the commonly held inference that shorter or zero-length embargoes will have a detrimental effect on publisher incomes (BIS Select ; but see also Jubb, 2011).…”
Section: Discuss This Articlementioning
confidence: 99%
“…These embargoes are applied in order to avoid putative reductions in subscription income due to such self-archiving." However, empirical evidence fails to support this 'obvious' claim, and we refer you to Berners-Lee et al, 2005;Swan, 2005;Henneken et al, 2007, Houghton et al, 2010, Bernius et al, 2013, and the Committee ), which all indicate that not only is there no loss of subscription for Economic Development, 2012 income from green open access, but that both can indeed coexist as a sustainable business model for publishers. Furthermore, there is little evidence to support the commonly held inference that shorter or zero-length embargoes will have a detrimental effect on publisher incomes (BIS Select ; but see also Jubb, 2011).…”
Section: Discuss This Articlementioning
confidence: 99%
“…Initially almost exclusively used by professional astronomers, the ADS now also has become a public service through external, general search engines (like Google, Yahoo, Microsoft Live Search and Ask.com, to name a few). Henneken et al (2007) observed that up to the middle of 2004, the number of ADS users doubled on a bi-yearly basis. Since the ADS started to be indexed by general search engines, the number of incidental users have increased dramatically.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 This model is already working in a number of subject areas, notably high-energy physics (a discipline with a well-established preprint culture) using arXiv. It is described by Henneken et al,8 who make the point that one of the reasons this model is sustainJournals and repositories: an evolving relationship?…”
Section: Model 1: 'Repository To Journal'mentioning
confidence: 99%